Improving an Organization Declining Performance - Anzalna, Raden Akbar; Welly, John (The Indonesian Journal of Business Administration, 2013)
PT Nusantara Turbin dan Propulsi (NTP) is one of trusted excellence center leading in South East Asia in the field of engineering, maintenance, repair and overhaul of gas turbines and rotating equipment. PT NTP has two strategic business units, namely Aero Engine Services and Industrial Turbine Services. PT NTP facing a problem in achieving the target in terms of revenue and timeliness of project completion that led to customer dissatisfaction and also there is geopolitical issue that affects the company financial performance. Those problems are the overcome challenges of the company in the future. In accordance with those problems, this final project will discuss improvements an organization declining performance. Two methods were used to find out problem that occurred at NTP, first is quantitative; by distributed questionnaires among fulltime employees, and second is qualitative; by conduted interviews with managers and employees. Questionnaires spread to Managers, Supervisor, and Staffs were aims to analyze level of organization, groups, and individual. Organization criteria (by Mckinsey) are strategy, structure, system, skill, staff, style, and shared values. Group (by Thomas Cummings and Cristopher Worley) are task structure, group composition, team functioning, and group norms. Individual (by McShane and Von Glinow) motivation, ability, role of perception, and situational factors. To improve an organization declining performance, organization can be diagnosed at three different levels, namely individual level, group level, and organizational level. Those three levels are the main factor to improve an organization declining performance. Based on this analysis, it can be determined the level of organization that led to a declining performance of organization. The result of the analysis of the information obtained from PT NTP concluded that the level of organizational is the causes of the organization declining performance. The analysis that conducted is by improving the elements that derived from the Mckinsey 7-S framework, namely strategy, system, structure, skill, staff, style, and shared values. The implementation plan of those improvements is applied using the eight-step model of change from John P. Kotter.Â Keywords: Organization declining performance, organizational level, Mckinsey 7-S framework